Right Ventricle Function in Patients with Acute Coronary Syndrome and Concomitant Undiagnosed Chronic Obstructive Pulmonary Disease. (4th July 2019) - Pavasini, Rita; Fiorencis, Andrea; Tonet, Elisabetta; Gaudenzi, Eleonora; Balla, Cristina; Maietti, Elisa; Biscaglia, Simone; Papi, Alberto; Ferrari, Roberto; Contoli, Marco; Campo, Gianluca
Abstract: Chronic obstructive pulmonary disease (COPD) is frequently undiagnosed in patients with ischemic heart disease. Nowadays, it is still unknown whether undiagnosed concomitant COPD is related to early structural changes of the heart, as detectable by trans-thoracic echocardiography (TTE). Starting from the study population of the Screening for COPD in ACS Patients (SCAP) trial, we sought to investigate potential differences in echocardiographic parameters in patients with acute coronary syndromes (ACS), with or without undiagnosed concomitant COPD. Overall, 137 patients were included. Undiagnosed COPD was detected by spirometry in 39 (29%) patients. TTE was performed at inclusion (before hospital discharge) and after six months. Several echocardiographic parameters including fractional area change (FAC) and RV strain (RVS), were measured. Patients with undiagnosed COPD, as compared to those without COPD, showed lower FAC and reduced RVS both at inclusion (37 ± 6% vs. 44 ± 9%, p  < 0.001; −15 ± −4 vs. −20 ± −5, p  < 0.001, respectively) and after six months (38 ± 7% vs. 45 ± 9%, p  < 0.001; −16 ± −4 vs. −20 ± −5, p  < 0.001, respectively). After multivariate analysis undiagnosed COPD was independently associated with lower FAC and reduced RVS at baseline and at TTE after six months. Early impairment of RV function can be detected in ACS patients with concomitant undiagnosed COPD. If these alterations may be changed by an early diagnosis and an early treatment, should be evaluated in future studies.Clinical trial registration: NCT02324660.